Upaya Meningkatkan Manajemen Waktu Melalui Bimbingan Klasikal Model Project Based Learning (PjBL) pada Siswa Sekolah Menengah Atas - Bayu Prasetya; Hardi Prasetiawan (Bulletin of Counseling and Psychotherapy, 2022)
This research is a Guidance and Counseling Action Research (PTBK). Action research is essentially a series of "actions" carried out in a series of problem solving. This study examines the problem of student time management which is still low. Next, action is given in the form of implementing a classical model project based learning (PjBL) guidance service. this research was conducted at the high school Srijaya Negara Palembang. The research subjects were students of class XI MIPA 1 who collected 33 students who experienced problems related to time management and teacher performance which had to be developed in the classical guidance service of the Project Based Learning (PjBL) model. The results of the research carried out were obtaining a significant increase in value, with an average pre-cycle result of 47%, cycle I: 68%, cycle II: 87%. From the results of the study it can be said that the classical model of Project Based Learning (PjBL) guidance services in an effort to improve the time management of students in class XI MIPA 1 Srijaya Negara Palembang High School experienced an increase in students' time management.